Association between long-term exposure to ambient particulate matter and pulmonary function among men and women in typical areas of South and North China - Liu, Qihang; Pan, Li; Yang, Ting; Ou, Qiong; Sun, Zhiwei; He, Huijing; Hu, Yaoda; Tu, Ji; Lin, Binbin; Lao, Miaochan; Liu, Chang; Li, Baicun; et al. (Frontiers in Public Health, 2023)
Background: Studies comparing the effects of different sizes and concentrations of ambient particulate matter (PM) on pulmonary function in different regions and sexes remain sparse. Objectives: To investigate the associations of different sizes and levels of long-term ambient PM exposure with pulmonary function among people of different sexes in typical areas of China. Methods: In 2021, a total of 1592 participants aged 20–73 years were recruited to participate in the pulmonary function test from the baseline survey of the Diverse Life-Course Cohort (DLCC) in typical areas of Guangdong Province and Hebei Province. The three-year (2018–2020) average ambient PM concentrations were assessed from the ChinaHighPM1 dataset, TAP dataset and ChinaHighPM10 dataset. Mean differences in pulmonary function were used in generalized linear models for different regions and sexes. Results: We discovered significant associations of ambient PM exposure with reduced forced vital capacity (FVC) and increased forced expiratory volume in one second (FEV1)/FVC among men and lower levels of FEV1 and FVC among women, such that a 5-μg/m3 concentration increase in PM1, PM2.5, and PM10 was associated with decreases in FVC of 123.5 mL (95% confidence interval (CI): 36.6, 210.3), 53.9 mL (95% CI: 15.7, 92.2) and 43.9 mL (95% CI: 15.1, 72.6) and increases in FEV1/FVC of 1.4 % (95% CI: 0.4, 2.5), 0.6 % (95% CI: 0.1, 1.1) and 0.5 % (95% CI: 0.1, 0.8) among men and decreases in FEV1 of 60.9 mL (95% CI: 20.7, 101.1), 25.0 mL (95% CI: 7.2, 42.8) and 19.9 mL (95% CI: 6.8, 33.0) and in FVC of 71.3 mL (95% CI: 20.7, 121.7), 37.4 mL (95% CI: 16.8, 58.0) and 25.0 mL (95% CI: 8.6, 41.4) among women in Hebei Province. There was no association between ambient PM and pulmonary function in Guangdong Province. Conclusions: Long-term exposure to different sizes and concentrations of ambient PM were associated with FEV1 and FVC among men and women differently. The impact of ambient PM on FVC should of greater concerned.